2009
DOI: 10.1587/transinf.e92.d.2454
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Inherent Pen Input Modalities for Precision Parameter Manipulations during Trajectory Tasks

Abstract: SUMMARYAdjustment of a certain parameter in the course of performing a trajectory task such as drawing or gesturing is a common manipulation in pen-based interaction. Since pen tip information is confined to x-y coordinate data, such concurrent parameter adjustment is not easily accomplished in devices using only a pen tip. This paper comparatively investigates the performance of inherent pen input modalities (Pressure, Tilt, Azimuth, and Rolling) and Key Pressing with the non-preferred hand used for precision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Subjects performed fastest using PU method, and performed slowest using EV method. Post hoc pairwise comparisons found significant difference (p < .05) between all nLevels pairs except (7, 8) (p = 0.28), (8,9) (p = 0.14), and (10, 11) (p = 0.67). A repeated measures analysis of variance showed that block had a significant effect on selection time (F 2, 16 = 13.42, p < .001).…”
Section: ) Selection Timementioning
confidence: 92%
See 1 more Smart Citation
“…Subjects performed fastest using PU method, and performed slowest using EV method. Post hoc pairwise comparisons found significant difference (p < .05) between all nLevels pairs except (7, 8) (p = 0.28), (8,9) (p = 0.14), and (10, 11) (p = 0.67). A repeated measures analysis of variance showed that block had a significant effect on selection time (F 2, 16 = 13.42, p < .001).…”
Section: ) Selection Timementioning
confidence: 92%
“…Ren et al [8] proposed the Adaptive Hybrid Cursor to facilitate target selection performance by automatically adjusting cursor size according to pen pressure. Xin and Ren [9] implemented a widget to manipulate high precision parameters. They comparatively investigated the performance of inherent pen input modalities (pen pressure, tilt, azimuth, and rolling) used for precision parameter manipulation during pen sliding actions and found that pen azimuth exhibited the worst performance.…”
Section: Related Workmentioning
confidence: 99%